Design and Implementation of a New High Security Text Encryption Algorithm Strengthened by Mathematical Methods - Demir, Hüseyin; Acar, Hünkar (Fırat University, 2025)
In this study, a hybrid encryption method is designed to address the shortcomings in well-known traditional encryption methods such as DES (Data Encryption Standard), AES (Advanced Encryption Standard), and Hill cipher. Unlike conventional methods, this new approach offers an innovative solution that fills the gaps in existing encryption techniques. The result is a more secure, flexible, and efficient encryption method. By providing a more complex and unpredictable encryption process, the resilience against attacks will be significantly increased. Consequently, a highly secure encryption algorithm will be created, suitable for various fields such as daily communications and military communications. This method emerges as a combination of classical and modern encryption techniques. By integrating the mechanical structure of classical rotor machines with the mathematical foundations of modern symmetric algorithms, this method not only revives historical encryption methodologies but also meets the security requirements of today. In this study, the security requirements of encryption and the height level will be discussed with probability calculation. Furthermore, the integration of modular arithmetic and rotor mechanisms increases complexity and unpredictability, offering an effective encryption and a stronger defence mechanism against cryptanalysis techniques through this hybrid method.

Bu çalışmada iyi bilinen geleneksel DES (Data Encryption Standard), AES (Advanced Encryption Standard) ve Hill vb. şifreleme yöntemlerinde meydana gelen eksiklikleri gidermek amacı ile geleneksel yöntemlerden farklı olarak yenilikçi ve mevcut şifreleme yöntemlerindeki boşluklara cevap verebilecek karma bir şifreleme yönteminin tasarımı verilmiştir. Bu yöntem sayesinde daha güvenilir, esnek ve performanslı bir şifreleme yöntemi elde edilecektir. Böylece daha karmaşık ve öngörülemez bir şifreleme süreci sağlayarak saldırılara karşı dayanıklılık artacaktır. Bu sayede günlük konuşmalar ve askeri haberleşmeler gibi çeşitli alanlarda kullanılabilecek güvenliği yüksek bir şifreleme algoritması oluşturulacaktır. Bu yöntem klasik ve modern şifreleme tekniklerinin bir kombinasyonu olarak ortaya çıkmaktadır. Klasik rotor makinelerinin mekanik yapısı ile modern simetrik algoritmaların matematiksel temellerini bir araya getiren bu yöntem hem tarihsel şifreleme metodolojilerini canlandırmakta hem de günümüz güvenlik gereksinimlerini karşılamaktadır. Bu güvenlik gereksinimleri ve yükseklik düzeyi olasılık hesabı ile gösterilecektir. Ayrıca, modüler aritmetik ve rotor mekanizmalarının entegrasyonu, karmaşıklığı ve öngörülemezliği artırarak, kriptanaliz tekniklerine karşı hem etkili bir şifreleme hem de daha güçlü bir savunma mekanizmasına sahip bir karma yöntem sunmaktadır.
Matematiksel Yöntemlerle Güçlendirilmiş Yeni Bir Yüksek Güvenlikli Metin Şifreleme Algoritmasının Tasarımı ve Uygulanması
Keywords: Information Security and Cryptology; Bilgi Güvenliği ve Kriptoloji; Cryptography; Kriptografi